Ipea em cinco tempos: Evidências sobre os concursos públicos de técnicos de planejamento e pesquisa do Instituto de Pesquisa Econômica Aplicada - André Gambier Campos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The objective of this discussion paper is to provide empirical evidence regarding public selections, which took place in the 1990s and 2000s, for planning and research technicians (TP) at the Institute for Applied Economic Research (Ipea). The objective is to provide evidence on various aspects, such as the attractiveness of each selection or the socio-demographic profiles and socio-work trajectories of the candidates, which have changed significantly over time. This discussion paper is part of a recent context, in which a new selection was authorized to select 80 new TP. Even though this event is already underway, an analysis of previous processes, from the 1990s and 2000s, can afford interesting elements to its understanding.
Keywords: H10; H83; Z13; 330; Institute for Applied Economic Research; public selections